Are dual action antidepressants superior than selective antidepressants? Part II - Czernikiewicz, Andrzej (Current Problems of Psychiatry, 2011)
Depression is a complex disease with some psychiatric comorbidities, especially anxiety disorders and some comorbid physical symptoms.During the past few years, there has been a strong interest in the development of dual-action antidepressants with a better side effect profile. There are interesting pharmacological reasons why an antidepressant that act on more that one neurotransmitter system might have superior efficacy than antidepressant with single action. There also is an increasing body of evidence for an efficacy advantage in some patients with selective dual-action antidepressants, especially in large group of patients with high manifestation of physical symptoms of depression. Dual-acting antidepressants that inhibit reuptake of both serotonin and norepinephrine (SNRIs) treat a wider array of depressive symptoms (psychological and physical) than antidepressants that target either neurotransmitter alone. SNRIs such as venlafaxine, and duloxetine, may have an earlier onset of action, superior remission abilities, and better efficacy in treating anxiety symptoms of depression than the SSRIs. The remission rates of the patients taking venlafaxine were significantly higher than those of the patients taking SSRIs, regardless of age or gender. Overall, dual-acting agents appear to be more effective than single-acting agents in improving mood, reducing pain, and increasing the chance of remission.